Kepemimpinan yang Efektif Dapat Meningkatkan Kinerja - Saepulloh, Maman (Jurnal Dirosah Islamiyah, 2025)
This study aims to examine the contribution of education policy and effective leadership to improving teacher performance and the quality of educational institutions in Indonesia. Using a qualitative approach based on a literature review of eight national journals, it was found that transformational and instructional leadership play an important role in building a positive work climate and improving teacher competence. Meanwhile, participatory and adaptive education policies have proven to be more effective than top-down approaches. The limitation of this study lies in its conceptual nature, which has not been empirically validated, but it offers an original contribution in the form of a systematic integration of leadership and education policy into a conceptual model. In conclusion, the harmonization of relevant policies and inspirational leadership is the key to successful improvement of education quality.